ANALISIS PARTISIPASI MASYARAKAT DALAM MENUNJANG PEMBANGUNAN DESA DI KECAMATAN TONGAUNA KABUPATEN KONAWE - Ishak, Fistarisma; Rostin, Rostin; Nusantara, Ambo Wonua (JURNAL EKONOMI UHO, 2016)
This study aims to determine the level of public participation and factors that effects the level of public participation on development of Tongauna District, Konawe Regency. Data collected through interviews and questionnaires with 60 respondents. The results showed that public participation in development of District of Tongauna for all indicators considered good enough. In the other sides, there are some problem that effects on public participation in Tongauna District, consits: the lack of knowledge, times, and jobs.